2021
DOI: 10.3390/cancers13225662
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins: Physiology, Colorectal Cancer Development, and Nanomediated Applications

Abstract: Tetraspanins are transmembrane proteins expressed in a multitude of cells throughout the organism. They contribute to many processes that surround cell–cell interactions and are associated with the progress of some diseases, including cancer. Their crucial role in cell physiology is often understated. Furthermore, recent studies have shown their great potential in being used as targeting molecules. Data have suggested the potential of tetraspanins as a targeting vector for nanomediated distribution and deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 87 publications
(103 reference statements)
3
13
0
Order By: Relevance
“…Clinically approved drugs often have limitations in target accumulation due to their lack of specificity, resulting in modest efficacy and numerous adverse effects. To enhance their potential, researchers utilize various targeting molecules, with Tspan proteins exhibiting significant promise in this regard [ 109 ]. Yue et al were the first to demonstrate the binding of Andrographis paniculata water (APW), including its components Andrographis paniculata Lactone, Andrographis paniculata A, and Andrographis paniculata C, to Tspan28, resulting in the inhibition of its function.…”
Section: The Role Of the Tspan Protein Family In Cancer Treatmentmentioning
confidence: 99%
“…Clinically approved drugs often have limitations in target accumulation due to their lack of specificity, resulting in modest efficacy and numerous adverse effects. To enhance their potential, researchers utilize various targeting molecules, with Tspan proteins exhibiting significant promise in this regard [ 109 ]. Yue et al were the first to demonstrate the binding of Andrographis paniculata water (APW), including its components Andrographis paniculata Lactone, Andrographis paniculata A, and Andrographis paniculata C, to Tspan28, resulting in the inhibition of its function.…”
Section: The Role Of the Tspan Protein Family In Cancer Treatmentmentioning
confidence: 99%
“…In the context of cancer, tetraspanins have been implicated in tumor progression, metastasis, and resistance to therapy [5,6]. By forming protein complexes with various cell surface molecules, such as integrins and receptors, tetraspanins participate in the progression and metastasis of various cancers, including CC (Scheme S1, Supplementary File S1) [5,7,8]. In CC, various studies have shown specific expressions of some tetraspanins in CC cell lines and bulk tissues, indicating their potential as diagnostic markers and therapeutic Life 2024, 14, 126 2 of 16 targets [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…By forming protein complexes with various cell surface molecules, such as integrins and receptors, tetraspanins participate in the progression and metastasis of various cancers, including CC (Scheme S1, Supplementary File S1) [5,7,8]. In CC, various studies have shown specific expressions of some tetraspanins in CC cell lines and bulk tissues, indicating their potential as diagnostic markers and therapeutic Life 2024, 14, 126 2 of 16 targets [7,9,10]. Some tetraspanins, such as TSPAN8 and CD151, have been associated with advanced tumor stage, metastasis, and poor clinical outcomes [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past ten years, the implication of tetraspanins in cancer has been largely documented and several of these proteins are considered as valid targets for the design of novel anticancer agents. They are particularly adapted to the treatment of colorectal cancer, hepatocellular carcinoma, gastric cancer and other types of solid tumors [ 6 , 7 , 8 , 9 ]. These proteins are also considered in onco-hematology, notably for the treatment of acute myeloid leukemia (AML) and lymphoma [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are over 33 tetraspanins in humans, plus non-conventional forms generated by alternative splicing [ 3 , 15 ]. Many of these tetraspanins are involved in cancers, chiefly TSPAN1, TSPAN8, TSPAN 13, CD9, CD37, CD63, CD81, CD82 and CD151 [ 6 ]. The latter protein CD151 can be targeted with monoclonal antibodies to block both primary tumor growth and metastasis in xenograft cancer models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%